A critical method for natural history: the development of Kant’s teleological principle - Cooper, Andrew (Faculdade de Filosofia e Ciências, 2018)
In recent years Kant’s pre-critical work on natural history has gained significant attention. Scholars have recognised that Kant’s nebular hypothesis of the formation of the solar system, his identification of the Milky Way as a rotating galaxy, and his reproductive account of heredity make innovative contributions to key debates in eighteenth century natural history. Of course, none of these ideas are especially novel.